Understanding mucus modulation behavior of chitosan oligomers and dextran sulfate combining light scattering and calorimetric observations - Ferreira, Leonardo M.B.; Cardoso, Valéria M.O.; dos Santos Pedriz, Igor; Souza, Maurício P.C. [UNESP]; Ferreira, Natália N.; Chorilli, Marlus [UNESP]; Gremião, Maria P.D. [UNESP]; Zucolotto, Valtencir (Elsevier, 2023)
This study reports the fundamental understanding of mucus-modulatory strategies combining charged biopolymers with distinct molecular weights and surface charges. Here, key biophysical evidence supports that low-molecular-weight (Mw) polycation chitosan oligosaccharides (COSs) and high-Mw polyanion dextran sulfate (DS) exhibit distinct thermodynamic signatures upon interaction with mucin (MUC), the main protein of mucus. While the COS → MUC microcalorimetric titrations released ~14 kcal/mol and ~60 kcal/mol, the DS → MUC titrations released ~1200 and ~1450 kcal/mol at pH of 4.5 and 6.8, respectively. The MPT-2 titrations of COS → MUC and DS → MUC indicated a greater zeta potential variation at pH = 4.5 (relative variation = 815 % and 351 %, respectively) than at pH = 6.8 (relative variation = 282 % and 136 %, respectively). Further, the resultant binary (COS-MUC) and ternary (COS-DS-MUC) complexes showed opposite behavior (aggregation and charge inversion events) according to the pH environment. Most importantly, the results indicate that electrostatics could not be the driving force that governs COS-MUC interactions. To account for this finding, we proposed a two-level abstraction model. Macro features emerge collectively from individual interactions occurring at the molecular level. Therefore, to understand the outcomes of mucus modulatory strategy based on charged biopolymers it is necessary to integrate both visions into the same picture.
Keywords: Biopolymers; Mucoadhesion; Mucus-modulation; Mucus-penetration; Nano-bio interfaces; Polyelectrolyte complexes